Prereaders' eye movements during shared storybook reading are language-mediated but not predictive. Issue 5 (28th May 2018) - Luke, Steven G.; Asplund, Anna
ABSTRACT: When viewing a visual scene, eye movements are often language-mediated: people look at objects as those objects are named. Eye movements can even reflect predictive language processing, moving to an object before it is named. Children are also capable of making language-mediated eye movements, even predictive ones, and prediction may be involved in language learning. The present study explored whether eye movements are language-mediated in a more naturalistic task – shared storybook reading. Research has shown that children fixate illustrations during shared storybook reading, ignoring text. The present study used high-precision eye-tracking to replicate this finding. Further, prereader participants showed increased likelihood of fixating relevant storybook illustrations as words were read aloud, indicating that their eye movements were language mediated like the adult participants. Language-mediated eye movements to illustrations were reactive, not predictive, in both participant groups.